(untitled) (Revista Latino-Americana de Enfermagem, 2011)
The aim of the study was to assess the trend of the infant mortality rate between 1990-2004 and the neonatal mortality between 2000-2005 in infants born at less than 32 weeks of gestational age or with very low birth-weight. Based on secondary data, infant mortality rate and by its component for Valdivia city were compared with national indicators. Mortality at